Social determinants of telemedicine utilization in ambulatory cardiovascular patients during the COVID-19 pandemic. Issue 2 (9th April 2021) - Brown, Kemar J; Mathenge, Njambi; Crousillat, Daniela; Pagliaro, Jaclyn; Grady, Connor; Katz, Nava; Singh, Jagmeet P; Bhatt, Ami B
Abstract: Aims: The coronavirus disease 2019 (COVID-19) pandemic has resulted in the rapid uptake of telemedicine (TM) for routine cardiovascular care. To examine the predictors of TM utilization among ambulatory cardiology patients during the COVID-19 pandemic. Methods and results: In this single-centre retrospective study, all ambulatory cardiovascular encounters occurring between 16 March and 19 June 2020 were assessed. Baseline characteristics by visit type (in-person, TM phone, TM video) were compared using Chi-square and student t -tests, with statistical significance defined by P -value <0.05. Multivariate logistic regression was used to explore the predictors of TM vs. in-person care. A total of 8446 patients [86% Non-Hispanic (NH) White, 42% female, median age 66.8 ± 15.2 years] completed an ambulatory cardiovascular visit during the study period. TM phone ( n  = 4981, 61.5%) was the primary mode of ambulatory care followed by TM video ( n  = 2693, 33.2%). NH Black race [odds ratio (OR) 0.56, 95% confidence interval (CI): 0.35–0.94; P -value = 0.02], Hispanic ethnicity (OR 0.53, 95% CI: 0.29–0.98; P  = 0.04), public insurance (Medicaid OR 0.50, 95% CI: 0.32–0.79; P  = 0.003, Medicare OR 0.65, 95% CI: 0.47–0.89; P  = 0.009), zip-code linked median household income of <$75 000, age >85 years, and patients with a diagnosis of heart failure were associated with reduced access to TM video encounters and a higher likelihood of in-person care. Conclusions: Significant disparities in TM video access for ambulatory cardiovascular care exist among the elderly, lower income, as well as Black and Hispanic racial/ethnic groups. Graphical Abstract: